P50 Localisation of the glycolytic isozyme, pyruvate kinase m2 in the lung of idiopathic pulmonary fibrosis. (15th November 2017) - Tan, S; Forty, EJ; Durrenberger, PF; McAnulty, RJ; Chambers, RC; Mercer, PF
Abstract : Introduction: Idiopathic pulmonary fibrosis (IPF) is the most common form of interstitial lung disease, with a poor prognosis and a lack of therapeutic options that halt disease progression. While the aetiology of IPF is unknown, dysregulated epithelial and mesenchymal response following persistent epithelial insult is thought to be critical in driving fibrosis. Recent evidence suggests that, akin to cancer, metabolic reprogramming may be important in driving many of these processes. In both cancer and fibrosis development, inducible expression of the pyruvate kinase isoform M2 (PKM2) represents an important adaptation for increasing the availability of glycolytic intermediates for biosynthesis and cell proliferation. Aim: We aim to investigate the expression of PKM2 in relation to cell-specific markers in the IPF lung. Methods: We used immunohistochemistry (IHC) and immunofluorescent (IF) co-staining approaches involving cell-specific markers αSMA (myofibroblast), CK7 (epithelium) and CD68 (infiltrating cells e.g., macrophages) in formalin fixed paraffin embedded (FFPE) lung tissues from IPF patients (n=3). Results: Using both immunoperoxidase and immunofluorescence co-staining, we have demonstrated PKM2 expression in both the CK7 positive bronchial epithelium, as well as the CK7 positive epithelium overlying fibrotic foci in lungs from IPF patients. PKM2 was also co-localised with CD68 positive infiltrating macrophage populations. Occasional examples of PKM2 positive staining were observed in αSMA-positive myofibroblasts. Conclusions: PKM2 expression was observed in epithelium and infiltrating macrophages, thought to be critically involved in the pathology of IPF. These data suggest that these cells may rely on aerobic glycolysis to provide for their biosynthetic requirements, and provide a foundation for studies to investigate the role of glycolytic reprogramming in lung injury and fibrosis.